Mercury stocks and methylmercury production remain unaffected by 17 years of experimental permafrost thaw - Haugk, Charlotte; Azaroff, Alyssa; Bertilsson, Stefan; Johansson, Margareta; Liu, Tong; Thompson, Lauren; Jonsson, Sofi (Frontiers in Environmental Chemistry, 2026)
Mercury (Hg) has been stored in permafrost peatlands for millennia. As permafrost thaw is predicted to increase with ongoing climate warming, Hg is at risk to be remobilized from those peatlands and hotspots for Hg methylation could potentially form. Monomethylmercury (MeHg) is a known neurotoxin and a health concern to northern communities if Hg is remobilized, transformed to MeHg and subsequently bioaccumulated in the food chain. It is uncertain how Hg cycles in thawing permafrost systems and how much of it could potentially be remobilized by thaw processes. In this study, we have investigated Hg dynamics in a permafrost peatland of northern Sweden, where a snow fence field experiment was set up in 2005 to simulate accelerated permafrost thaw through winter warming. We compared total mercury (THg) and MeHg concentrations in soil plots representing intact and thawed permafrost conditions, investigated seasonal variations and examined the coupling between microbial community composition and MeHg concentration. Similar stocks of both total THg and MeHg were observed in intact and thawed permafrost conditions, suggesting that 17 years of winter warming manipulation and accelerated permafrost thaw had not led to substantial Hg loss from the peat nor extensive MeHg production. The apparent stability of the Hg stocks contrasted with our hypothesis and with many previous studies. While there was no difference in microbial communities between treatments with or without accelerated thaw, putative methylators were more abundant in thaw plots in the fall. This indicates that permafrost thaw has increased the potential for Hg methylation, although these shifts have not yet been strong enough to measurably affect MeHg stocks. Our study emphasizes the complexity of Hg dynamics in thaw-affected permafrost landscapes and the need to consider thaw-related perturbations of the Hg cycle on various timescales.